2020
DOI: 10.1002/ppp.2036
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicle‐based mapping of turf‐banked solifluction lobe movement and its relation to material, geomorphometric, thermal and vegetation properties

Abstract: Solifluction is one of the most widespread periglacial processes with low annual movement rates in the range of —millimeters to centimeters. Traditional methods to assess solifluction movement usually have low spatial resolution, which hampers our understanding of spatial movement patterns and the factors controlling them. In this study, we (a) test the applicability of unmanned aerial vehicle (UAV)‐based structure‐from‐motion photogrammetry in comparison to a traditional total station survey to map surface mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
0
10
1
Order By: Relevance
“…Alongside, new developments in the domain of image processing and photogrammetric techniques, such as structure from motion (SfM), have burgeoned during the last years (James and Robson, 2012;Westoby et al, 2012;Smith et al, 2016;Anderson et al, 2019). As such, the so-called UAV-SfM photogrammetric workflows have been used in different domains, such as the monitoring of landslide kinematics (Lucieer et al, 2013;Clapuyt et al, 2017) and for studying glacial (Ryan et al, 2015;Fugazza et al, 2018;Rossini et al, 2018;Benoit et al, 2019) and periglacial processes (Eichel et al, 2020;Hendrickx et al, 2020), among other applications. Until now, only a few study cases have reported on rock glacier monitoring by relying exclusively on UAV-SfM techniques (Dall'Asta et al, 2017;Vivero and Lambiel, 2019;Halla et al, 2021;Bearzot et al, 2022) or by a combination of UAV-SfM with additional remote sensing data (Kaufmann et al, 2018;Groh and Blöthe, 2019;Fey and Krainer, 2020;Blöthe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside, new developments in the domain of image processing and photogrammetric techniques, such as structure from motion (SfM), have burgeoned during the last years (James and Robson, 2012;Westoby et al, 2012;Smith et al, 2016;Anderson et al, 2019). As such, the so-called UAV-SfM photogrammetric workflows have been used in different domains, such as the monitoring of landslide kinematics (Lucieer et al, 2013;Clapuyt et al, 2017) and for studying glacial (Ryan et al, 2015;Fugazza et al, 2018;Rossini et al, 2018;Benoit et al, 2019) and periglacial processes (Eichel et al, 2020;Hendrickx et al, 2020), among other applications. Until now, only a few study cases have reported on rock glacier monitoring by relying exclusively on UAV-SfM techniques (Dall'Asta et al, 2017;Vivero and Lambiel, 2019;Halla et al, 2021;Bearzot et al, 2022) or by a combination of UAV-SfM with additional remote sensing data (Kaufmann et al, 2018;Groh and Blöthe, 2019;Fey and Krainer, 2020;Blöthe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most geomorphometric studies have focused on fluvial, glacial, and arid geomorphic landscapes (e.g., [68][69][70] ). Applications of geomorphometry in the periglacial realm, although of long standing (e.g., 45,[71][72][73][74][75][76][77][78][79] ), are scattered widely and do not form a cohesive body of literature, particularly with respect to erosional landforms. As in other areas of geomorphometry, a locus has developed in periglacial geomorphometric research involving the use of DEMs, often in concert with remotely sensed products.…”
Section: Hypsometry and Periglacial Geomorphometrymentioning
confidence: 99%
“…Other potential applications may include, for instance, studies of alluvial fans [68], glacial landforms [40,69], glacier lake outburst floods [70,71] or aeolian landforms [72][73][74]. Furthermore, the scripts can be used for modelling various small objects, e.g., in archaeology [75] or geomorphology [76]. The presented scripts enabled a quick launch and systematic work, thereby making it possible to process more efficiently, e.g., several dozen large sets of images in agriculture [77], where each field can be used as a separate point of interest.…”
Section: Potential Applicationsmentioning
confidence: 99%